ФОРМУВАННЯ ГОТОВНОСТІ СТУДЕНТІВ ДО ТВОРЧОЇ ДІЯЛЬНОСТІ ЯК ФАКТОР РОЗВИТКУ ОСОБИСТОСТІ B ПРОЦЕСІ ДИРИГЕНТСЬКОЇ ПІДГОТОВКИ (Педагогіка вищої та середньої школи, 2007)
The article deals with the problem of actuality in demanol formation of personality self-realization, notional knowledge in philosophical and psychological and pedagogical literature is made up.